Mothers Knowledge Toward Correct Infant Sleep Practices and Sudden Infant Death Syndrome In Al-Najaf Provence - Miaad Jasim Mohammed Alzubaidi, Abeer Miri Abdullah, Farah Sadiq Abd Hashem, Alaq Hameed Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: "The current study aims to assess the proportion of newborns that sleep well and investigates the awareness and comprehension of SIDS and its associated risk factors among mothers of infants in Al Najaf Provence". Methodology: In order to accomplish the study’s goals, a descriptive cross-sectional study was used throughout. The study took place between November 2021 and February 2022. a Non-Probability (Purposive Sample) of 100 moms who arrived with infants (under 1 year old) at the Hospital for Maternity and Children and the primary healthcare facilities in Al-Najaf Provence. Results: The study’s findings revealed that (49%) of newborns were found to be sleeping on their sides, (37%) were found to be dozing off, and (14%) were found to be sleeping on their prone backs. Participants as a whole (60%) stated that (40%) child doctors were the main information source they used to learn about SIDS. Conclusion: In our study, women had limited understanding about sudden infant death syndrome, and a substantial percentage of them were unaware that smoking exposure during pregnancy and after delivery had been linked to an elevated risk of SIDS. In our study, a large percentage of moms were unaware that giving their babies pacifiers while they slept reduced the risk of SIDS. Keywords: knowledge, mother, sudden infant death syndrome.